Sessile oak (Quercus petraea (Mattuschka) Liebl.) trees variability according to an analysis of multispectral images taken from UAV – first results - Będkowski, Krzysztof; Stereńczak, Krzysztof (Ecological Questions, 2013)
The paper presents first results of the use of multispectral aerial images to identify the outum phenophases of sessile oak. Observed phenophases are represented with three leaf colors – green, yellow and brown. Color composition of images in three spectral bands: blue, green and red, taken by digital non metric Sigma DP2 cameras, which were carried by Unmanned Aerial Vehicle (UAV) were used. Pictures were taken on 17 October 2011. Two observers made visual crowns classification of 556 oak trees into three groups: green, yellow and brown, on the basis of the dominant color of the leafs. It was found that among observers there is a large compliance in classification (79.7%). Additionally, observations of the spring growth of leafs on 54 trees crowns images recorded from seven positions were evaluated. Although the results may indicate the existence of certain trends, the clear relationship between autumn and spring phases of trees growing can not be noted now (due to small number of sample and short time of observations). The use of UAV to monitor the length of the individual tree growing season has been confirmed.